The Concept of Human Inner World in Russian Bylinas - O V Klypa (Peoples' Friendship University of Russia (RUDN University), 2012)
The article gives a psychological analysis of the Russian bylinas as a special kind of historical sources for the study of ordinary psychological conceptions; being a product of collective creativity of the people, they reflect a wide range of psychological concepts and experiences of man.